Extracurricular Activity Involvement on the Compassion, Academic Competence, and Commitment of Collegiate Level Students: A Structural Equation Model - Boy, Imary Frances (Animo Repository, 2022)
Extracurricular activities (ECAs) performed outside the realm of a student’s academic activities such as sports, drama, music, and dance play an integral part in their educational experience and positive youth development. Nevertheless, there is a paucity of studies exploring the interrelationship of ECA involvement on the compassion, academic competence, and commitment of collegiate students. Hence, this study determined the influence of ECA involvement on the compassion, academic competence, and commitment of collegiate students. Employing a covariance-based structural equation modeling, a descriptive-correlational design was conducted among 365 consenting collegiate students who completed standardized instruments to measure their ECAs profile, compassion, academic competence, and commitment. Results showed that the breadth of ECA involvement, which refers to the total number of organizations that a respondent is a member of, had an indirect, positive effect on compassion (β = 0.06, p < 0.05) and commitment (β = 0.06, p < 0.05) and a direct, negative influence on academic competence (β = −0.14, p < 0.05). Although social- and arts-related ECAs promoted compassion (β = 0.16, p < 0.01) and commitment (β = 0.26, p < 0.05), respectively, sports-related ECAs deterred academic competence (β = −0.12, p < 0.05). The model highlights that although ECA involvement may bring positive outcomes, participation in numerous organizations may hinder academic competence, an understanding that accentuates the need for institutional policies and guidelines on ECA involvement of collegiate students.